Can inhibition or shifting training enhance cognitive abilities in emerging adults? - Podlesek, Anja (Psihološka obzorja (Ljubljana), 2021)
Executive functions enable and support most of our daily cognitive functioning. Within the number of executive functions proposed, updating, inhibition and shifting are most often considered as the three core executive functions. Cognitive training paradigms provide a platform for a possible enhancement of these functions. Since updating training has been studied to a greater extent, we wanted to investigate the effectiveness of inhibition and shifting training in this study. Emerging adults (psychology students) were randomly assigned either to the inhibition training (based on the Simon task; n = 36) or to the shifting training (based on the task switching paradigm; n = 35). Both groups underwent twelve 20-minute sessions distributed over four weeks. Measurements before and after the training included criterion tasks (i.e. the training tasks), near-transfer tasks (i.e. tasks that address the trained functions but use different types of stimuli or rules to respond), and far-transfer tasks (i.e., tasks that address untrained cognitive functions). The control participants (n = 36) were tested with a combination of these tasks. Both training groups improved their criteria task performance over time, while convincing training-related gains were not found in either near- or far-transfer tasks. This study raises some conceptual questions for the training of executive functions with respect to a sample of emerging adults with above-average cognitive abilities, motivational elements of training, and the role of executive functions in more complex everyday cognitive activities.
Keywords: brain training; cognitive ability; cognitive processes; cognitive psychology; emerging adulthood; executive function; inhibicija; inhibition; izvršilne funkcije; kognitivna psihologija; kognitivni procesi; kognitivni trening; prehod v odraslost; preklapljanje; spoznavne sposobnosti; task switching; The Simon task; The task switching paradigm